Association between sleep duration and risk of nonalcoholic fatty liver disease: A systematic review and meta-analysis - Kasra Pirahesh; Ali Zarrinnia; Leila Nikniaz; Zeinab Nikniaz (Preventive Medicine Reports)
Introduction: Considering that both long and short sleep duration may have an association with nonalcoholic fatty liver disease (NAFLD), in this meta-analysis, we analyzed the dose-response association between sleep duration and NAFLD along with meta-analyses of the differences in mean sleep duration between NAFLD patients and healthy controls, and linear meta-analysis of the association between sleep duration and NAFLD. Methods: PubMed (665 articles), Scopus (442 articles), and Web of Sciences (200 articles) were searched from inception until November 2023. Observational studies were included if they assess the association between sleep duration and NAFLD or compare the mean sleep duration between patients with NAFLD and healthy population. All studies done in humans without restriction on sex, age, and language were included. The methological quality of studies was assessed by Joanna Briggs Institute (JBI) tools. The meta-analysis was conducted using STATA. Results: Thirty-one studies that included 836,117 participants were included in this systematic review. The results indicated no significant differences between NAFLD patients and healthy controls regarding mean sleep duration [Mean difference: -7.08, 95 % CI: −20.10, 5.94]. The subgroup meta-analysis did not show any significant differences between groups. The long versus short sleep duration meta-analysis showed a significant association between sleep duration and NAFLD (OR: 0.8 [95 % CI, 0.74–0.91]). The results of the dose-response meta-analysis do not suggest a linear or nonlinear relationship between sleep duration and NAFLD (p-value = 0.9). Conclusion: The highest category of sleep duration was associated with a lower risk of NAFLD. However, no dose-response association was observed.